Hyperoxia and antioxidants during major non‐cardiac surgery and risk of cardiovascular events: Protocol for a 2 × 2 factorial randomised clinical trial. Issue 3 (26th December 2019) - Petersen, Cecilie; Loft, Frederik C.; Aasvang, Eske K.; Vester‐Andersen, Morten; Rasmussen, Lars S.; Wetterslev, Jørn; Jorgensen, Lars N.; Christensen, Robin; Meyhoff, Christian S.
Abstract : Background: Myocardial injury after non‐cardiac surgery occurs in a high number of patients, resulting in increased mortality in the post‐operative period. The use of high inspiratory oxygen concentrations may cause hyperoxia, which is associated with impairment of coronary blood flow. Furthermore, the surgical stress response increases reactive oxygen species, which is involved in several perioperative complications including myocardial injury and death. Avoidance of hyperoxia and substitution of reactive oxygen species scavengers may be beneficial. Our primary objective is to examine the effect of oxygen and added antioxidants for prevention of myocardial injury assessed by area under the curve for troponin measurements during the first three post‐operative days. Methods: The VIXIE trial (VitamIn and oXygen Interventions and cardiovascular Events) is an investigator‐initiated, blinded, 2 × 2 factorial multicentre clinical trial. We include 600 patients with cardiovascular risk factors undergoing major non‐cardiac surgery. Participants are randomised to an inspiratory oxygen fraction of 0.80 or 0.30 during and for 2 hours after surgery and either an intravenous bolus of vitamin C and an infusion of N‐acetylcysteine or matching placebo of both. The primary outcome is the area under the curve for high‐sensitive cardiac troponin release during the first three post‐operative days as a marker of the extent of myocardial injury. Secondary outcomes are mortality, non‐fatal myocardial infarction and non‐fatal serious adverse events within 30 days. Perspective: The current trial will provide further evidence for clinicians on optimal administration of perioperative oxygen in surgical patients with cardiovascular risks and the clinical effects of two common antioxidants.